rút gọn biểu thức: a)M=90.10^n-10^n+2+10^n+1 b)P=y(x^n-1+y^n-1)-x^n-1(x+y)

Question

rút gọn biểu thức:
a)M=90.10^n-10^n+2+10^n+1
b)P=y(x^n-1+y^n-1)-x^n-1(x+y)

in progress 0
Alexandra 2 tuần 2021-09-08T13:59:59+00:00 2 Answers 1 views 0

Answers ( )

    0
    2021-09-08T14:01:33+00:00

    Đáp án:

     

    Giải thích các bước giải:

     

    0
    2021-09-08T14:01:51+00:00

    Đáp án:

     

    Giải thích các bước giải:

    a(M=90.10^n-10^n+2+10^n+1

    M=90.10^n +(10^n-10^n)+(2+1)

    M=90.10^n+3

    b)P=y.x^n-1 + y^n-x^n-x-y

    P=y^n+1+(x^n – 3)y-x^n – x

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )